2015
DOI: 10.1186/s13006-015-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum women’s use of medicines and breastfeeding practices: a systematic review

Abstract: The objectives of this article are to systematically review i) the extent of medicine use in postpartum women, and ii) the impact of maternal medicine use (excluding contraceptives and galactogogues) on breastfeeding outcomes (initiation and/or duration). PubMed, Medline (Ovid), Scopus (Elsevier), Cinahl (EBSCO), PsycINFO (Ovid), Embase (Ovid) and Web of Science (ISI) databases were searched to find original studies on medicine use in women after the birth. Additional studies were identified by searching Googl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 51 publications
4
74
0
Order By: Relevance
“…Breastfeeding practices can be affected by several historical, socioeconomic, cultural and individual factors [24]. During the sensitive period after childbirth, many women face health problems requiring the use of medications [6]. Although the most commonly used medications are considered safe during lactation and the adverse effects due to the maternal use of medications in breastfed children are rare, their use can be perceived as a barrier for breastfeeding for many reasons, especially due to misinterpretation of risk and pressures faced by the breastfeeding woman [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breastfeeding practices can be affected by several historical, socioeconomic, cultural and individual factors [24]. During the sensitive period after childbirth, many women face health problems requiring the use of medications [6]. Although the most commonly used medications are considered safe during lactation and the adverse effects due to the maternal use of medications in breastfed children are rare, their use can be perceived as a barrier for breastfeeding for many reasons, especially due to misinterpretation of risk and pressures faced by the breastfeeding woman [10].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, in our findings, there was no statistically significant difference in weaning rates between women who did not consume medications or consumed only breastfeeding-compatible medications and among women who took medicines that pose some risk to milk production or risks for the child, for both criteria. Nowadays, there are few studies evaluating the duration of breastfeeding regarding the use of medicines [6,10]. A study carried out in Brazil using American Academy of Pediatrics classification for medicines' compatibility with breastfeeding (2001) and Hale's criteria (2004) with a sample of 246 women showed that duration of breastfeeding was longer in women who did not use any medication or who used only medicines compatible with breastfeeding [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show that women take more medications during breastfeeding compared to pregnancy. It is necessary to advise and fi nd alternative ways to prevent ending breastfeeding 14 .…”
Section: Contraceptionmentioning
confidence: 99%
“…Surveys in different countries show that 90–99% of women take at least one drug in the postpartum period , and up to 5% of them take medications to treat chronic conditions (e.g. epilepsy, thyroid disorders, diabetes, hypertension and psychiatric conditions) . Since initiating and maintaining breastfeeding is crucial in the immediate postpartum setting, it is important to ensure that sufficient information exists about the pharmacokinetics and safety profiles of medications taken by the mother.…”
Section: Antecedents and Pharmacoepidemiologymentioning
confidence: 99%